Fluorite type high-entropy oxide catalyst as well as preparation method and application thereof

By adopting fluorite-type high-entropy oxide catalysts, the existing RWGS catalysts have been solved, efficient CO2 conversion and good thermal stability have been achieved, and significant industrial application potential.

CN119500100APending Publication Date: 2025-02-25ORDOS HEYUAN TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411678313.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing RWGS catalysts have low activity and poor stability, making it difficult to effectively carry out CO2 conversion reaction under high temperature conditions.

Method used

A fluorite-type high-entropy oxide catalyst is used, with specific components of x% ZnO/AO2, and A is five transition metal elements: Ce, Zr, Y, La and Ti. It is prepared by citric acid complexing and high-temperature calcination to form a catalyst with high configuration entropy and good thermal stability.

Benefits of technology

In the RWGS reaction under 500-550°C, the CO2 conversion rate reaches more than 40%, the CO selectivity reaches 100%, and good stability is maintained during long-term operation, with good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500100A_ABST
    Figure CN119500100A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and discloses a fluorite type high-entropy oxide catalyst and a preparation method and application thereof.The molecular formula of the fluorite type high-entropy oxide catalyst is shown as x% ZnO / AO2, A is ions of five transition metal elements including Ce, Zr, Y, La and Ti, and the five transition metal elements are equal in molar content; the configuration entropy Sconfig of the fluorite type high-entropy oxide catalyst is greater than or equal to 1.61 R; wherein the molar fraction x% of the auxiliary agent ZnO is in a range of 0-30%; the preparation method comprises the following steps: dissolving metal nitrate containing A-type elements, zinc nitrate, citric acid and ethylene glycol in distilled water to obtain a mixed solution; stirring the mixed solution to obtain gel, and calcining the dry gel to obtain the fluorite type high-entropy oxide catalyst. The high-entropy oxide AO2 and ZnO serving as an auxiliary are applied to the reverse water-gas shift reaction of carbon dioxide as catalysts, and good activity, selectivity and stability are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular, relates to an oxide catalyst and a preparation method and application thereof. Background Art

[0002] High entropy oxide (HEO) is an emerging material in recent years, showing research value in thermal catalysis, photocatalysis, electrocatalysis, etc. High entropy oxide (HEO) refers to five or more quasi-molecular metal elements arranged in an orderly manner in a randomly distributed single-phase lattice, which increases the configuration entropy (S config ≥1.61R) to stabilize the structure. After forming a single-phase HEOs with a cubic or hexagonal lattice, a high temperature treatment (such as >1000°C) can hardly destroy the structure, so it has excellent thermal stability and is suitable for use as a catalyst or catalyst carrier for high-temperature reactions. Existing high-entropy oxides include a variety of crystal structures such as rock salt, spinel, fluorite, perovskite and solid solution, and have broad development and application prospects.

[0003] The current problems of energy shortage and environmental pollution can be solved by CO 2 The capture and utilization technology can solve this problem. The reverse water gas shift reaction (RWGS, CO 2 +H 2 =CO+H 2 O) is a way to utilize carbon dioxide hydrogenation. The reaction product CO is an important chemical raw material and can produce many products, such as methanol through hydrogenation reaction, straight-chain hydrocarbons through Fischer-Tropsch synthesis, etc. At present, the catalytic reaction of CO to methanol has entered a new stage. Some researchers have tried to complete the reverse water gas shift reaction and the subsequent CO to methanol reaction on a catalyst at the same time, and have achieved certain results. In addition, the production of C 2+ The chemical is CO 2 The important direction of utilization is CO and H 2 The syngas composed of C is synthesized into polycarbons through the Fischer-Tropsch reaction. 2+ In general, CO 2 The CO produced by the RWGS reaction has important application prospects. It can not only develop a circular economy but also promote environmental protection, killing two birds with one stone.

[0004] There are two main categories of catalysts reported for the reverse water gas shift reaction: supported metal catalysts and oxide catalysts. The supported active metals are mainly Ni, Ru, Rh, Cu, Pt, Co, Fe, and Au. Among them, Ru and Rh-based noble metal catalysts generally have excellent CO 2Conversion rate and CO selectivity, but the cost is too high, and it is necessary to consider reducing the precious metal loading to achieve industrial application as soon as possible; Ni, Co, Cu, Fe and other metal catalysts have relatively excellent catalytic activity and relatively low price, and have application potential, but the reverse water gas reaction is an endothermic reaction, and it requires high temperature conditions to achieve a suitable conversion rate and selectivity. Its thermal stability is the key; the relatively new Pt and Au-based precious metal catalysts have just started research in this field. Based on their precious metal characteristics, the research and application prospects are broad. The activity of supported metal catalysts comes from multiple pathways such as the characteristics of the active metal itself, strong metal-support interaction (SMSI), the role of additives, and the formation of bimetallic. Compared with supported active metal catalysts, metal oxide catalysts often have good thermal stability due to their structural characteristics, do not sinter, and are not easy to coke, and have unique advantages. The research on metal oxide catalysts for RWGS reactions has gone through early single oxide catalysts and later composite oxide catalysts; their development and utilization focuses on the oxide effects of inactive metal components such as Ce, Zn, Al, Zr, Cr, La, Mn, Ti, and the amplification of catalytic properties such as oxygen vacancies and alkaline sites by composite configurations such as solid solutions, spinels, and perovskites. In general, supported active metal catalysts often have good activity and selectivity, but the thermal stability of supported metals is difficult to solve; and traditional single metal oxides or metal oxide catalysts doped with a second type of metal face challenges in terms of activity or selectivity. Therefore, considering high entropy oxides of multiple metal components as catalysts, we can not only obtain the stability given by high configurational entropy, but also explore the excellent activity and stability brought by the selection of different metal components, and the development prospects are broad. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of low activity and poor stability of existing RWGS catalysts, and to provide a fluorite-type high entropy oxide catalyst and a preparation method thereof, which can be used as a catalyst in the RWGS reaction and exhibit good activity and stability.

[0006] According to one aspect of the present invention, a fluorite-type high entropy oxide catalyst is provided, whose molecular formula is expressed as x% ZnO / AO 2 , A is an ion of five transition metal elements, Ce, Zr, Y, La, and Ti, and the five transition metal elements have equimolar contents; the configuration entropy S of the fluorite-type high entropy oxide catalyst is config ≥1.61R; wherein the molar fraction x% of the auxiliary agent ZnO is in the range of 0% to 30%.

[0007] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned fluorite-type high entropy oxide catalyst, comprising the following process:

[0008] (1) dissolving a metal nitrate containing a type A element, zinc nitrate, citric acid and ethylene glycol in deionized water to obtain a mixed solution;

[0009] (2) stirring the mixed solution obtained in step (1) in a water bath at 60-100° C. with magnetic force until a gel is obtained, and then drying to obtain a xerogel;

[0010] (3) calcining the dry gel obtained in step (2) at 300-400° C. for 1-3 h, and then heating to 750-850° C. for calcining for 2-6 h to obtain a fluorite-type high entropy oxide catalyst.

[0011] Furthermore, in step (1), the metal nitrate containing type A elements is composed of cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, and tetrabutyl titanate.

[0012] Furthermore, in step (1), the molar ratio of the total amount of the metal nitrate containing the A-type element and the zinc nitrate, the citric acid, and the ethylene glycol is 1:(1-2):(0.2-1).

[0013] Furthermore, it is characterized in that in step (2), the drying temperature is 80-120° C. and the drying time is 8-16 hours.

[0014] Furthermore, in step (3), the heating rate of the two calcinations is 1-5°C / min.

[0015] According to another aspect of the present invention, there is provided an application of the above-mentioned fluorite-type high entropy oxide catalyst in reverse water-gas shift.

[0016] Furthermore, as a catalyst, carbon dioxide and hydrogen are introduced into the reactor at a temperature of 500-550° C. and a pressure of 1-5 MPa.

[0017] Furthermore, the volume space velocity of the carbon dioxide and hydrogen is 9000-24000 mL / (g cat h).

[0018] Furthermore, the molar ratio of carbon dioxide to hydrogen is 1:(3-4).

[0019] The beneficial effects of the present invention are:

[0020] (i) The fluorite-type high entropy oxide catalyst of the present invention can be used as a catalyst by itself, or a ZnO auxiliary agent can be added to act as a catalyst, so as to give full play to the "cocktail" effect of the high entropy oxide and obtain excellent activity and selectivity. Other metal oxides can also be added as auxiliary agents in the future, and the performance prospect is broad; at the same time, its own characteristics give it a "high entropy" effect, and it has excellent thermal stability and stable performance.

[0021] (ii) The fluorite-type noble oxide of the present invention is prepared by citric acid complexation combined with high-temperature calcination. The method is simple and easy to operate. At the same time, the prepared high-entropy oxide is in powder form and the metal elements are evenly dispersed.

[0022] (III) The present invention utilizes the excellent thermal stability of high-entropy fluorite oxide, good dispersibility of metal ions, and the synergistic redox effect of its surface defects, oxygen vacancies, and multiple metal ions; structurally avoids the aggregation of metal ions; the prepared high-entropy fluorite oxide component does not contain obvious H 2 It is not reduced to metal components, but through the screening of metal components and the construction of fluorite structure. It can be applied to the reverse water gas shift reaction and show good activity and selectivity. 2 The conversion rate can reach more than 40%, the CO selectivity can reach 100%, and the stability can run well for 100 hours at a reaction temperature of 550°C without obvious performance degradation, which has considerable prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the XRD diagram of the catalyst prepared in Examples 1-15 of the present invention.

[0024] Figure 2 It is a performance diagram of the reverse water gas reaction of the catalyst prepared by Examples 1-15 of the present invention.

[0025] Figure 3 1 is the XRD diagram of the catalysts prepared in Examples 16-27 of the present invention.

[0026] Figure 4 It is a performance diagram of the reverse water gas reaction of the catalysts prepared in Examples 16-27 of the present invention.

[0027] Figure 5 3. It is the XRD diagram of the catalyst prepared in Example 28 of the present invention before and after the stability test.

[0028] Figure 6 This is a performance diagram of the reverse water-gas reaction of the catalyst prepared in Example 28 of the present invention in a stability test.

[0029] Figure 7 3 is the XRD diagram of the catalyst prepared in Example 29 of the present invention before and after the stability test.

[0030] Figure 8 This is a performance diagram of the reverse water gas reaction of the catalyst prepared in Example 29 of the present invention in a stability test. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and drawings.

[0032] Example 1

[0033] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:1:0.2.

[0034] 2) The prepared mixed salt solution was stirred and evaporated in a 60° C. water bath to obtain a gel, and then dried in an oven at 80° C. for 8 h to obtain a xerogel.

[0035] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 850°C and calcined for 2h to obtain catalyst Ce. 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 2 -850.

[0036] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 9000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 39.5% and the CO selectivity was 96.6%.

[0037] Example 2

[0038] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:1.2:0.2.

[0039] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0040] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 850°C and calcined for 4h to obtain catalyst Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 2 -850.

[0041] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 40.3% and the CO selectivity was 97.6%.

[0042] Example 3

[0043] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:2:0.4.

[0044] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0045] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 850°C and calcined for 6h to obtain catalyst Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 2 -850.

[0046] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 39.4% and the CO selectivity was 96.8%.

[0047] Example 4

[0048] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.18:0.18:0.18:0.18:0.18:0.18:0.1:1.2:0.2.

[0049] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0050] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 850°C and calcined for 2h to obtain a catalyst 10% ZnO / Ce 0.2 Zr0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0051] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO 2 The conversion rate was 55.4% and the CO selectivity was 96.9%.

[0052] Example 5

[0053] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.18:0.18:0.18:0.18:0.18:0.18:0.1:1.2:0.2.

[0054] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0055] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 850°C and calcined for 4h to obtain a catalyst 10% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0056] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 56.3% and the CO selectivity was 97.3%.

[0057] Example 6

[0058] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.18:0.18:0.18:0.18:0.18:0.1:2:1.

[0059] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0060] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 850°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0061] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 46.5% and the CO selectivity was 93.8%.

[0062] Example 7

[0063] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1:0.2.

[0064] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0065] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 850°C and calcined for 2h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0066] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 9000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. 2 The conversion rate was 33.9% and the CO selectivity was 99.2%.

[0067] Example 8

[0068] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0069] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0070] 3) After drying, the product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 850°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0071] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 58.2% and the CO selectivity was 100%.

[0072] Example 9

[0073] 1) Dissolve cerium nitrate, zirconium nitrate, ammonium molybdate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:2:0.4.

[0074] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0075] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 850°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0076] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cath) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO 2 The conversion rate was 57.2% and the CO selectivity was 98.3%.

[0077] Example 10

[0078] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.15:0.15:0.15:0.15:0.15:0.25:1:0.2.

[0079] 2) The prepared salt solution was stirred and evaporated in a 60° C. water bath to obtain a gel, which was then dried in an oven at 80° C. for 812 h.

[0080] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 850°C and calcined for 2h to obtain a catalyst 25% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0081] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 56.8% and the CO selectivity was 98.5%.

[0082] Embodiment 11

[0083] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.15:0.15:0.15:0.15:0.15:0.25:1.2:0.2.

[0084] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0085] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 850°C and calcined for 4h to obtain a catalyst 25% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti0.2 O 0.2 -850.

[0086] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 58.6% and the CO selectivity was 100%.

[0087] Example 12

[0088] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.15:0.15:0.15:0.15:0.15:0.25:2:1.

[0089] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0090] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 850°C and calcined for 6h to obtain a catalyst 25% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0091] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 57.9% and the CO selectivity was 98.8%.

[0092] Example 13

[0093] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.14:0.14:0.14:0.14:0.14:0.3:1:0.2.

[0094] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0095] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 850°C and calcined for 2h to obtain a catalyst 30% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0096] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 9000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 34.9% and the CO selectivity was 100%.

[0097] Embodiment 14

[0098] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.14:0.14:0.14:0.14:0.14:0.3:1.2:0.2.

[0099] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0100] 3) After drying, the product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 850°C and calcined for 4h to obtain a catalyst 30% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0101] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 58.4% and the CO selectivity was 100%.

[0102] Embodiment 15

[0103] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.14:0.14:0.14:0.14:0.14:0.3:2:0.4.

[0104] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0105] 3) The dried product was heated to 300°C at 5°C / min and calcined for 3h, and then continued to be heated to 850°C and calcined for 6h to obtain a catalyst 30% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -850.

[0106] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO 2 The conversion rate was 57.4% and the CO selectivity was 98.2%.

[0107] Example 16

[0108] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0109] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0110] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 550°C and calcined for 2h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -550.

[0111] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cath) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 41.1% and the CO selectivity was 100%.

[0112] Embodiment 17

[0113] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0114] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0115] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 550°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -550.

[0116] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 60.0% and the CO selectivity was 100%.

[0117] Embodiment 18

[0118] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:2:1.

[0119] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0120] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 550°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2O 0.2 -550.

[0121] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 57.8% and the CO selectivity was 99.0%.

[0122] Embodiment 19

[0123] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1:0.2.

[0124] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0125] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 650°C and calcined for 2h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -650.

[0126] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 9000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 42.3% and the CO selectivity was 96.2%.

[0127] Embodiment 20

[0128] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0129] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0130] 3) After drying, the product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 650°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -650.

[0131] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 60.3% and the CO selectivity was 98.5%.

[0132] Embodiment 21

[0133] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:2:0.4.

[0134] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0135] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 650°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -650.

[0136] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO 2 The conversion rate was 58.4% and the CO selectivity was 97.8%.

[0137] Embodiment 22

[0138] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0139] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0140] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 750°C and calcined for 2h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -750.

[0141] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 9000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 57.6% and the CO selectivity was 98.1%.

[0142] Embodiment 23

[0143] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0144] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0145] 3) After drying, the product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 750°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -750.

[0146] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cath) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 59.0% and the CO selectivity was 100%.

[0147] Embodiment 24

[0148] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:2:1.

[0149] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0150] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 750°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -750.

[0151] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 57.4% and the CO selectivity was 98.2%.

[0152] Embodiment 25

[0153] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1:0.2.

[0154] 2) The prepared salt solution was stirred and evaporated in a 60°C water bath to obtain a gel, which was then dried in an oven at 80°C for 8 h.

[0155] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, and then continued to be heated to 950°C and calcined for 2h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O0.2 -950.

[0156] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO 2 The conversion rate was 57.2% and the CO selectivity was 97.8%.

[0157] Embodiment 26

[0158] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0159] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0160] 3) After drying, the product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 950°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -950.

[0161] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 58.7% and the CO selectivity was 100%.

[0162] Embodiment 27

[0163] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:2:0.4.

[0164] 2) The prepared salt solution was stirred and evaporated in a 100° C. water bath to obtain a gel, which was then dried in an oven at 120° C. for 16 h.

[0165] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 950°C and calcined for 6h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -950.

[0166] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO 2 The conversion rate was 57.4% and the CO selectivity was 97.4%.

[0167] Embodiment 28

[0168] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, zinc nitrate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.16:0.16:0.16:0.16:0.16:0.2:1.2:0.2.

[0169] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0170] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 550°C and calcined for 4h to obtain a catalyst 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 0.2 -550.

[0171] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: At the beginning of the stability test, the CO 2 The conversion rate was 59.7%. As time went by, the conversion rate decreased slowly. By 100h, CO 2The conversion rate dropped to 52.4%, with a cumulative decrease of 7.3% within 100 hours, and no obvious plateau period appeared; in addition, the CO selectivity of the reaction kept fluctuating between 98-100% during the 100-hour stability test, and no stable CO selectivity was shown.

[0172] Embodiment 29

[0173] 1) Dissolve cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol in deionized water to prepare a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:1.2:0.2.

[0174] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C to obtain a gel, which was then dried in an oven at 120°C for 12 hours.

[0175] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 850°C and calcined for 4h to obtain catalyst Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 2 -850.

[0176] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) A reverse water-gas shift reaction test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: At the beginning of the stability test, the CO 2 The conversion rate was 42.7%. As the test progressed, the conversion rate data first slowly decreased and then increased and remained stable until 100h. At the end, CO 2 The conversion rate was 40.8%, with a cumulative decrease of 1.9% within 100 hours, and an obvious conversion rate plateau appeared; in addition, the CO selectivity of the reaction remained at 97.5% except for a few points during the stability test, and its value was very stable.

[0177] The products of step 3) of Examples 2, 5, 8, 11, and 14 of the present invention were subjected to XRD analysis to obtain the XRD pattern of the catalyst after calcination. Figure 1 .from Figure 1 It can be seen that the catalyst prepared in Example 2 calcined at 850°C forms a fluorite structure; Figure 1It can be seen that the catalysts prepared in Examples 5, 8, 11, and 14 with ZnO as an additive not only formed a fluorite structure, but also had a ZnO characteristic peak, that is, the ZnO phase existed on the fluorite high entropy oxide. Comparing the XRD diagram after the reaction, it can be seen that the fluorite structure of the catalyst prepared in Example 2 was well preserved after the reaction, and the fluorite structure showed good thermal stability; at the same time, the catalysts containing ZnO additives prepared in Examples 5, 8, 11, and 14 still had both the fluorite structure and the ZnO phase after the reaction, indicating that the addition of the additive ZnO did not reduce the stability of the catalyst.

[0178] 0.2 g of the product after step 3) of Examples 2, 5, 8, 11, and 14 of the present invention was taken for a reverse water gas reaction test. The reaction pressure was 3 MPa and the reaction temperature was 300-550° C. The composition of the reaction gas was analyzed by gas chromatography. The corresponding CO 2 Conversion and CO selectivity data, obtained Figure 2 .from Figure 2 It can be seen that the CO 2 The conversion rate increases with the increase of temperature, reaching a peak of 40% at a reaction temperature of 550°C, and its CO selectivity is basically at the level of 100%. c The reaction temperature is 97.6%, and the selectivity is excellent; Figure 2 It can be seen that the CO 2 The conversion rate is significantly higher than that of the catalyst without additives, but does not change significantly with the amount of ZnO additive added. It can reach 58% at a reaction temperature of 550°C, and its CO selectivity is basically 100%, which is also excellent. In general, the reverse water gas shift catalysts prepared in Examples 2, 5, 8, 11, and 14 have good activity and excellent selectivity.

[0179] The products of step 3) of Examples 8, 17, 20, 23, and 26 of the present invention were subjected to XRD analysis to obtain the XRD pattern of the catalyst after calcination. Figure 3 .from Figure 3 It can be seen that the catalysts prepared in Examples 17 and 20 calcined at 550°C and 650°C did not form a fluorite structure, and the presence of the ZnO phase was not observed. Figure 3 It can be seen that the catalysts prepared in Examples 23 and 8 calcined at 750°C and 850°C formed a fluorite structure and a ZnO phase, and as the calcination temperature increased, the ZnO characteristic peak tended to become sharper, that is, a slight grain growth occurred. Figure 3It can be seen that the catalyst prepared by Example 26 calcined at 950°C forms a fluorite structure and a ZnO phase, and also forms a non-fluorite characteristic peak, that is, the oxide is not a single fluorite phase, and a fluorite-type high entropy oxide catalyst cannot be formed. Comparing the XRD diagrams after the reaction, it can be seen that the catalysts prepared by Examples 17 and 20 have a weak fluorite phase and a ZnO phase after the reaction, that is, the thermal stability of the catalyst calcined at a low temperature is general; while the catalysts prepared by Examples 23, 8, and 26 still have a good fluorite structure and a ZnO phase after the reaction, indicating that the fluorite structure calcined at a high temperature has good thermal stability.

[0180] 0.2 g of the product after step 3) of Examples 8, 17, 20, 23, and 26 of the present invention was taken for a reverse water gas reaction test. The reaction pressure was 3 MPa and the reaction temperature was 300-550° C. The composition of the reaction gas was analyzed by gas chromatography. The corresponding CO 2 Conversion and CO selectivity data, obtained Figure 4 .from Figure 4 It can be seen that the CO 2 The conversion rate is roughly the same, and basically does not fluctuate greatly with the change of calcination temperature, reaching 58% at a reaction temperature of 550°C; for CO selectivity, the catalysts prepared in different embodiments all show an almost complete 100% level, and only the catalyst calcined at 650°C is 97% in the temperature range of 500-550°C. In general, the fluorite-type high entropy oxide catalyst with 20% ZnO additive has good activity and excellent selectivity.

[0181] The products of step 3) and step 4) of Example 28 of the present invention were subjected to XRD analysis to obtain XRD patterns of the catalyst after calcination and after reaction. Figure 5 As shown. Figure 5 It can be seen that the catalyst calcined at 550°C has no characteristic peak of fluorite, that is, no fluorite structure is formed. There is still no characteristic peak of fluorite in the X-ray diffraction spectrum after the reaction, but the characteristic peak of ZnO becomes sharper and the particles grow larger, that is, the catalyst structure without fluorite structure is unstable.

[0182] The results of the stability test of the reverse water gas reaction performed on Example 28 of the present invention are as follows: Figure 6 As shown: During the 100h test, CO 2 The conversion rate gradually decreased from 59.7% at the beginning to 52.4% at 100h, a decrease of 7.3%, which is a large decrease; at the same time, the CO selectivity kept changing and did not show a stable selectivity performance; in general, 20% ZnO / Ce 0.2 Zr 0.2 Y 0.2 La0.2 Ti 0.2 O 0.2 The -550 catalyst did not form a fluorite structure after low-temperature calcination, and the stability test showed that it did not have good thermal stability.

[0183] The products of step 3) and step 4) of Example 29 of the present invention were subjected to XRD analysis respectively to obtain XRD patterns of the catalyst after calcination and after reaction. Figure 7 As shown. Figure 7 It can be seen that the catalyst calcined at 850°C has a fluorite characteristic peak and forms a fluorite structure. After the stability test, the fluorite characteristic peak still exists well, that is, the 100-h stability reaction test did not destroy the fluorite structure, indicating that the high-entropy oxide with a fluorite structure is structurally stable and has good thermal stability.

[0184] The results of the stability test of the reverse water gas reaction performed on Example 29 of the present invention are as follows: Figure 8 As shown: Within the 100h range of the stability test, CO 2 The conversion rate began to fluctuate between 40% and 42%, which may be caused by insufficient reaction. Within 20 to 100 hours, CO 2 The conversion rate was always maintained at a level above 40.8%, and the conversion rate level was very stable; the CO selectivity was basically maintained at a level of 97.6% to 97.9% during the test period, and the selectivity level was also very stable; in general, the catalyst Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O 2 The fluorite structure formed by high-temperature calcination of -850 gives the high-entropy oxide catalyst good thermal stability.

[0185] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A fluorite-type high entropy oxide catalyst, characterized in that: Its molecular formula is x% ZnO / AO2, A is ions of five transition metal elements, Ce, Zr, Y, La, and Ti, and the five transition metal elements have equal molar contents; the configuration entropy S of the fluorite-type high entropy oxide catalyst is config ≥1.61R; wherein the molar fraction x% of the auxiliary agent ZnO is in the range of 0% to 30%.

2. A method for preparing the fluorite-type high entropy oxide catalyst as claimed in claim 1, characterized in that: The process includes the following: (1) dissolving a metal nitrate containing a type A element, zinc nitrate, citric acid and ethylene glycol in deionized water to obtain a mixed solution; (2) stirring the mixed solution obtained in step (1) in a water bath at 60-100° C. with magnetic force until a gel is obtained, and then drying to obtain a xerogel; (3) calcining the dry gel obtained in step (2) at 300-400° C. for 1-3 h, and then heating to 750-850° C. for calcining for 2-6 h to obtain a fluorite-type high entropy oxide catalyst.

3. The method for preparing a fluorite-type high entropy oxide catalyst according to claim 2, characterized in that: In step (1), the metal nitrate containing type A elements is composed of cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate and tetrabutyl titanate.

4. The method for preparing a fluorite-type high entropy oxide catalyst according to claim 2, characterized in that: In step (1), the molar ratio of the total amount of the metal nitrate containing the A-type element and the zinc nitrate, the citric acid, and the ethylene glycol is 1:(1-2):(0.2-1).

5. The method for preparing a fluorite-type high entropy oxide catalyst according to claim 2, characterized in that: In step (2), the drying temperature is 80-120° C. and the drying time is 8-16 hours.

6. The method for preparing a fluorite-type high entropy oxide catalyst according to claim 2, characterized in that: In step (3), the heating rate of the two calcinations is 1-5°C / min.

7. Use of the fluorite-type high entropy oxide catalyst as claimed in any one of claims 1 to 2 in reverse water gas shift.

8. The use of a fluorite-type high entropy oxide catalyst in reverse water gas shift according to claim 7, characterized in that: As a catalyst, carbon dioxide and hydrogen are added into the reactor at a temperature of 500-550°C and a pressure of 1-5 MPa.

9. The use of a fluorite-type high entropy oxide catalyst in reverse water gas shift according to claim 8, characterized in that: The volume space velocity of carbon dioxide and hydrogen is 9000-24000mL / (g cat h).

10. The use of a fluorite-type high entropy oxide catalyst in reverse water gas shift according to claim 8, characterized in that: The molar ratio of carbon dioxide to hydrogen is 1:(3-4).

Citation Information

Cited By

  • Catalyst for reverse water gas shift reaction and preparation method thereof

    CN122321845A